Modifying Older Adults' Daily Sedentary Behaviour Using an Asset-based Solution: Views from Older Adults - Dawn A Skelton; Emmanuelle Tulle; Marlene Sandlund; Sebastien FM Chastin; Calum F Leask (AIMS Press, 2016)
Objective: There is a growing public health focus on the promotion of successful and active ageing. Interventions to reduce sedentary behaviour (SB) in older adults are feasible and are improved by tailoring to individuals' context and circumstances. SB is ubiquitous; therefore part of the tailoring process is to ensure individuals' daily sedentary routine can be modified. The aim of this study was to understand the views of older adults and identify important considerations when creating a solution to modify daily sedentary patterns. Method: This was a qualitative research study. Fifteen older adult volunteers (mean age = 78 years) participated in 1 of 4 focus groups to identify solutions to modify daily sedentary routine. Two researchers conducted the focus groups whilst a third took detailed fieldnotes on a flipchart to member check the findings. Data were recorded and analysed thematically. Results: Participants wanted a solution with a range of options which could be tailored to individual needs and circumstances. The strategy suggested was to use the activities of daily routine and reasons why individuals already naturally interrupting their SB, collectively framed as assets. These assets were categorised into 5 sub-themes: physical assets (eg. standing up to reduce stiffness); psychological assets (eg. standing up to reduce feelings of guilt); interpersonal assets (eg. standing up to answer the phone); knowledge assets (eg. standing up due to knowing the benefits of breaking SB) and activities of daily living assets (eg. standing up to get a drink). Conclusion: This study provides important considerations from older adults' perspectives to modify their daily sedentary patterns. The assets identified by participants could be used to co-create a tailored intervention with older adults to reduce SB, which may increase effectiveness and adherence.